Filling the health gap in energy performance certificates to reduce pulmonary diseases due to bad indoor air quality - Soares dos Reis, Alexandre (2022)
Good indoor air quality (IAQ) levels in buildings are among the essential benefits and drivers as they lead to better health and comfort of the occupants. However, this research identified a health gap in dwellings’ energy performance certificates (EPCs) in Portugal, as IAQ seems not to be appropriately covered. Volatile organic compounds (VOCs) are gases containing various chemicals emitted from liquids or solids. Additionally, biomass-burning stoves are significant contributors to fine particle matter (PM2.5) concentrations that may cause cancer and respiratory diseases. Therefore, it is crucial to formulate strategies to control and enhance IAQ. As air pollutants often enter the human body through inhalation, the respiratory system is regularly the main target of Indoor Air Pollution (IAP), resulting in pulmonary diseases and allergies. These facts emphasize the need to track IAQ properly. Depending on indoor air pollutants, several rules and criteria are the basis of the current published work on IAQ indicators. According to our findings, in the planning stage, understandable and straightforward criteria for VOCs, PM2.5, and proper ventilation schemes, could help architects and engineers to enhance IAQ. Finally, next-generation EPCs could consider the proposed IAQ score to fill the identified health gap.